Epidemiologia da Leishmaniose Visceral Canina no Sul do Estado de Santa Catarina - Leote, Diego Soares (2018)
Visceral leishmaniasis is a vector-borne parasitic disease that is among the most neglected diseases in the world. The disease affects children and immunosuppressed people, causing fever, weight loss and even death. The main reservoir of the disease is the domestic dog and monitoring the prevalence of the disease in dogs can prevent the increase of cases in humans. This study aimed to define the prevalence of Visceral Canine Leishmaniasis in a non - endemic region in the southern state of Santa Catarina, as well as to identify risk factors for infection. A cross - sectional study was carried out with dogs from Centers for Zoonoses Control of the cities of Tubarão and Criciúma. Blood samples were collected from 107 dogs that were analyzed by the real-time polymerase chain reaction method, and the characteristics of the canine population were observed through a questionnaire and physical examination. Of the total number of dogs collected, 20 animals were positive (19%), of which 17 dogs (85%) had no clinical signs of the disease. A higher positivity was observed in animals older than 7 years (33.3%) and in urban dwellers (23.3%). There was no difference between positive males and females, as well as between castrated and non-castrated females. None of the variables presented statistical significance when applied to the Pearson chi-square test. The main symptom identified in the observation were dermatopathies (84.2%). It is concluded that the prevalence of dogs positive for Visceral Canine Leishmaniasis in the study is higher than the prevalence compared to other regions considered non-endemic, showing that there is transmission of the disease in the studied population and that the high index of asymptomatic positives may contribute to the non-identification of cases.